2014
DOI: 10.1038/srep07251
|View full text |Cite
|
Sign up to set email alerts
|

Training improves visual processing speed and generalizes to untrained functions

Abstract: Studies show that manipulating certain training features in perceptual learning determines the specificity of the improvement. The improvement in abnormal visual processing following training and its generalization to visual acuity, as measured on static clinical charts, can be explained by improved sensitivity or processing speed. Crowding, the inability to recognize objects in a clutter, fundamentally limits conscious visual perception. Although it was largely considered absent in the fovea, earlier studies … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 89 publications
5
26
0
Order By: Relevance
“…For such a framework to support "vision at a glance" (Hochstein and Ahissar, 2002;Kubilius et al, 2014), it would be reasonable to assume that such pre-attentive computations should occur fast and based on coarse spatial resolution, as is the case with the magnocellular pathway (Schmolesky et al, 1998;Lamme and Roelfsema, 2000) which appears to function normally in LG (Gilaie-Dotan et al, 2009, 2011. Another such processing route that might also be normal in LG (see place recognition in Table 2), might rely on peripheral form-based computations, which are suggested to respond transiently (Gilaie-Dotan et al, 2008) and rely on coarse spatial resolution (Levy et al, 2001(Levy et al, , 2004Dumoulin and Wandell, 2008). This might actually suggest that local-global effects are driven by peripheral coarse vision integrating over space, possibly relying on the same mechanisms as those for place recognition.…”
Section: Open Questionsmentioning
confidence: 93%
See 2 more Smart Citations
“…For such a framework to support "vision at a glance" (Hochstein and Ahissar, 2002;Kubilius et al, 2014), it would be reasonable to assume that such pre-attentive computations should occur fast and based on coarse spatial resolution, as is the case with the magnocellular pathway (Schmolesky et al, 1998;Lamme and Roelfsema, 2000) which appears to function normally in LG (Gilaie-Dotan et al, 2009, 2011. Another such processing route that might also be normal in LG (see place recognition in Table 2), might rely on peripheral form-based computations, which are suggested to respond transiently (Gilaie-Dotan et al, 2008) and rely on coarse spatial resolution (Levy et al, 2001(Levy et al, , 2004Dumoulin and Wandell, 2008). This might actually suggest that local-global effects are driven by peripheral coarse vision integrating over space, possibly relying on the same mechanisms as those for place recognition.…”
Section: Open Questionsmentioning
confidence: 93%
“…I also include in this group three functions (matching static faces based on identity or expression, reading heavily masked text, and recognizing complex Kanizsa figures) that LG was impaired in before training, and was not tested on after training, as I find that their perceptual demands resemble those of tasks that LG is still impaired in (face perception, and shape recognition from incomplete information), yet I cannot rule out a possible post-training improvement, had LG been retested on these functions post-training. Explicitly, this group includes contrast sensitivity (Polat et al, 2005;Gilaie-Dotan et al, 2009;Lev et al, 2015), near and far visual acuity (Gilaie-Dotan et al, 2009;Lev et al, 2015), crowding (Bonneh et al, 2004;Gilaie-Dotan et al, 2009;Lev et al, 2015), lateral interactions (Polat and Sagi, 1993;GilaieDotan et al, 2009;Lev et al, 2014Lev et al, , 2015, identifying contour in noise (Kovacs et al, 2000;Gilaie-Dotan et al, 2009;Lev et al, 2015), Table 2). …”
Section: Visual Functions That Are Dependent On Intermediate Visualmentioning
confidence: 96%
See 1 more Smart Citation
“…The vast majority of this work has been carried out within individual sensory systems, and has shown that very simple sensory-based judgments and abilities, such as Vernier acuity (vision), frequency discrimination (auditory) and two-point discrimination (tactile), can be greatly improved using training approaches in which subjects are receiving feedback on the basis of their ongoing judgments (Kaas et al, 2013; Lev et al, 2014; Zaltz et al, 2010; Zhou et al, 2006). Although fascinating, these studies have also reinforced that these training-based improvements rarely extend beyond the trained task.…”
Section: Plasticity and Remediation Therapies In Asdmentioning
confidence: 99%
“…However, recent studies revealed a number of cases where perceptual learning can transfer to untrained tasks and stimuli910. In fact, a significant portion of the current research on perceptual learning is aimed toward elucidating conditions that facilitate generalization of perceptual training.…”
mentioning
confidence: 99%